EFEKTIVITAS PROGRAM PEMBERDAYAAN DUKUNGAN SUAMI SIAGA DALAM MELAKUKAN DETEKSI DINI PREEKLAMPSIA - Meinawati, Lusianah (Jurnal Insan Cendekia, 2024)
Introduction: Midwives as professionals in maternal and child health services must comply with midwifery service standards. The performance of midwives in implementing midwifery service standards has an impact and has leverage on the quality of antenatal services which further contributes to the reduction in morbidity and mortality rates in mothers and babies. The inability of midwives to provide 24-hour services in the village and find one by one pregnant women with preeclampsia is one of the causes of maternal and fetal deaths. The health condition of pregnant women in the village needs special attention, especially by the husband, a husband must be able to independently detect the health of pregnant women at home. Method: Pre-experimental research design type Pretes-Posttest Design. The subjects of the study were 44 husbands of pregnant women in the working area of the Jombang Regency Health Center, taken by Multistage random sampling technique. The exogenous variable of empowerment of husband support and the endogenous variable is the detection of preeclampsia. The instrument uses questionnaires. The collected data is then processed and analyzed with Wilcoxon statistical tests. Results: Wilcoxon's test results obtained a p-Value of 0.001. From the p-Value value of 0.001 (<0.005) shows that there is an effect of empowering standby husband support on early detection of preeclampsia Conclusion: There is a difference between the skill level of husbands in detecting high-risk pregnant women before and after health education in the implementation of pre-eclampsia screening, so that health education in the implementation of pre-eclampsia screening is effective in improving husbands' skills in detecting high-risk pregnant women. Keywords: Empowerment, Husband Alert, Early Detection, Preeclampsia